Contemporary issues in international trade : challenges and opportunities - Bhattacharyya, Rajib; Mazumdar, Debashis (Emerald Publishing Limited, 2024)
From the 2008 global financial crisis and the Covid-19 pandemic, to Brexit and the ongoing Russia-Ukraine war, the past two decades have been a turbulent period for the global economy. Recognising that we are currently at a tipping point, Contemporary Issues in International Trade: Challenges and Opportunities provides a comprehensive overview of the changes in trade and capital flows currently in play across the globe. Topics of discussion include: Vertical specialization Impact of crises on trade Macroeconomic vulnerability in developing countries India's automotive and technological exports The influence of liberalization on India's manufacturing sector International insurance markets Protectionism Labour market impact of trade reforms Blockchain technology The influence of 'fake news' on trading preferences Challenges in the globalisation of agriculture Correlations between trade and human development Reaching beyond the usual terrain of economic engagement, this edited collection confronts critical issues to demand urgent analytical attention and a harnessing of the economic potential at stake.